Structural and Physiological Exploration of Salmonella Typhi YfdX Uncovers Its Dual Function in Bacterial Antibiotic Stress and Virulence - Lee, Hye Seon; Lee, Soohyun; Kim, Jun-Seob; Lee, Hae-Ran; Shin, Ho-Chul; Lee, Moo-Seung; Jin, Kyeong Sik; Kim, Cheol-Hee; Ku, Bonsu; Ryu, Choong-Min; Kim, Seung Jun (Frontiers in Microbiology, 2019)
YfdX is a prokaryotic protein encoded by several pathogenic bacteria including Salmonella enterica serovar Typhi, which causes one of the most fatal infectious diseases, typhoid fever. YfdX is a product of the yfdXWUVE operon and is known to be under the control of EvgA, a regulator protein controlling the expression of several proteins involved in response to environmental stress, in Escherichia coli. Nevertheless, unlike other proteins encoded by the same operon, the structural and physiological aspects of YfdX have been poorly characterized. Here, we identified a previously unknown pH-dependent stoichiometric conversion of S. Typhi YfdX between dimeric and tetrameric states; this conversion was further analyzed via determining its structure by X-ray crystallography at high resolution and by small-angle X-ray scattering in a solution state and via structure-based mutant studies. Biologically, YfdX was proven to be critically involved in Salmonella susceptibility to two β-lactam antibiotics, penicillin G and carbenicillin, as bacterial growth significantly impaired by its deficiency upon treatment with each of the two antibiotics was recovered by chromosomal complementation. Furthermore, by using Galleria mellonella larvae as an in vivo model of Salmonella infection, we demonstrated that Salmonella virulence was remarkably enhanced by YfdX deficiency, which was complemented by a transient expression of the wild-type or dimeric mutant but not by that of the monomeric mutant. The present study work provides direct evidence regarding the participation of YfdX in Salmonella antibiotic susceptibility and in the modulation of bacterial virulence, providing a new insight into this pathogen’s strategies for survival and growth.